Pengaruh Komitmen Organisasi Terhadap Kinerja Pegawai di Kantor Sekretariat Daerah Kabupaten Aceh Barat - Arnia; Zhafira, Nabila Hilmy (Regress: Journal of Economics & Management, 2022)
Organizational commitment is belief in the organization and plays a role in realizing organizational goals and has a desire to continue to be in the organization, performance is the result of work done by someone in his business. The purpose of this research was to determine whether there is an effect of organizational commitment on employee performance in the West Aceh Regional Secretariat office. The data analysis used in this research is simple linear regression. Based on simple linear regression equation analysis and hypothesis testing, it is known that there is an influence between organizational commitment (X) and employee performance (Y), this is proven by a simple linear test which shows that organizational commitment has a positive effect on employee performance in the Secretariat office. From the t-test, organizational commitment has a positive and significant impact on employee performance. Meanwhile, the f-test also shows that organizational commitment has a significant effect on the performance of employees in the Secretariat office. And the result of the determinant coefficient explains that 30.8% of employee performance is influenced by indicators of organizational commitment.